2006
DOI: 10.1111/j.1467-9477.2006.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Fragmentation, Institutional Engineering and the Development of Elderlycare and Childcare in Sweden

Abstract: This article seeks to identify institutional causes behind policy‐specific retrenchments in the Swedish welfare state. During the austerity period of the 1980s and 1990s, the Swedish welfare state simultaneously experienced retrenchments in some fields and stability or expansion in others. Elderlycare is an example of tremendous retrenchment and childcare one of continuous expansion. A comparison of both fields suggests that the divergent trends might be related to different policy‐specific levels of instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Decentralization and welfare federalism may, on the other hand, ease the development and endurance of social programs. Local and regional authorities tend to be closer to the population and may be more receptive to social demands, and they may also act as veto points to retrenchment proposals (Obinger et al, ; Rauch, ) and as reform catalysts in areas where both the perception of need and support for reform is widespread (Costa‐Font, ).…”
Section: Welfare States Multilevel Governance and Long‐term Carementioning
confidence: 99%
“…Decentralization and welfare federalism may, on the other hand, ease the development and endurance of social programs. Local and regional authorities tend to be closer to the population and may be more receptive to social demands, and they may also act as veto points to retrenchment proposals (Obinger et al, ; Rauch, ) and as reform catalysts in areas where both the perception of need and support for reform is widespread (Costa‐Font, ).…”
Section: Welfare States Multilevel Governance and Long‐term Carementioning
confidence: 99%
“…Institutional fragmentation is when decision-making is fragmented, as occurred in Ghana, among administrative bodies instead of being concentrated in one oversight body (Meyer and Scott, 1992). It creates problems for policy makers in coordination, and in division and allocation of authority, responsibility, and accountability (Rauch, 2006). It also produces veto points that enable some institutions to undermine others in making and developing policy (Swank, 2001;Tsebelis, 1995).…”
Section: Performance Management and Performance Of Public Sector Instmentioning
confidence: 99%
“…Other studies have found that in this prioritisation sectors that are most dominated by national hierarchical instruments are prioritised (Rauch 2006).…”
mentioning
confidence: 98%